Wrapped in two flags : the commplex political history of Nunavik - Hervé, Caroline (American Review of Canadian Studies, 2017)
During the first half of the twentieth century, northern Quebec was under federal jurisdiction. Tired of English Canadian supremacy and increasingly aware of northern Quebec’s considerable natural resources, which could provide a solid basis for future moves toward independence, the Quebec government began to take over responsibility for its northern territories in the 1960s. It established a regional administration to take charge of its northern affairs and sent officers to northern Quebec’s remote communities. For two decades, both governments administered the region and imposed two political systems on the local Inuit. This article is based on lengthy fieldwork and archival research. The historical background is described to show how Nunavik has developed as a political and social entity through its relationships with the Quebec and Canadian governments. This conflictual situation has created tensions in the Inuit community, resulting in political dissensions over the goal of self-government. Finally, this article details how the Inuit have exploited federal–provincial tensions to further their own interests.